Effect of Zinc Supplementation on Changes in Anthropometric Index of Toddler: A Meta-Analysis - Usmaningrum, Desif Upix; Murti, Bhisma; Pamungkasari, Eti Poncorini (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Stunting occurs as a result of a long chain of malnutrition burden at every phase of life. Insufficient intake of protein energy in pregnancy and toddler growth has an impact on the risk of stunting under five. In addition, stunting is also considered to be closely related to deficiency of essential micronutrients, especially iron and zinc. Subjects and Method: This research is a systematic review and meta-analysis study using PRISMA diagrams. The article search was conducted based on the eligibility criteria using the PICO Model. Population: Infants aged 0-59 months, Intervention: Zinc supplementation, Comparison: Placebo, Outcome: Anthropometric index of height for age (HAZ). The articles used were from PubMed, Google Scholar, Science Direct, and Scopus published from 2016 – 2022. The keywords used in the search were “zinc” AND “height” AND “infant” OR “toddler”. The inclusion criteria in this study were full paper articles with Randomized Control Trial, the intervention given was zinc with placebo comparison, research subjects were infants aged 0 – 59 months, and articles were published in English. The final results are presented in Standardized Mean Difference (SMD) in the analysis using the Revman 5.3 application. Results: Meta-analysis was carried out on 10 articles originating from the continents of Asia, Africa, and America. The results of the analysis showed that zinc supplementation increased the anthropometric index (HAZ) with SMD=0.51 units higher than placebo and statistically significant (SMD=0.51, 95% CI=0.17 to 0.85; p=0.003). Conclusion: The results of the meta-analysis showed that the administration of zinc supplementation increased the anthropometric index (HAZ) in children under five. Keywords: zinc, anthropometry, height for age, toddler. Correspondence: Desif Upix Usmaningrum. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: desifupix@student.uns.ac.id. Mobile: +6287838887228.